Teacher’s Readiness in the New Principal Preparation Program (PPP) - Ratna Juwita; Siswandari Siswandari (International Journal of Pedagogy and Teacher Education, 2018)
This descriptive study reports on the learning readiness of teachers in the Indonesia Principal Preparation Programme (PPP). The Republic of Indonesia Ministry of Education and Culture has decreed that school principal candidates are to have school principal certificates before they can be appointed as school principals. The school principal certificate can only be attained by completing the PPP, one of the important stages of which is education and training. As a form of learning, education and training in the PPP demands school principal candidates to exhibit learning readiness. It has long and widely been acknowledged that learning readiness is one of the most important determining factors of success in learning. The PPP itself, in short, is a programme designed to equip teachers with previously determined competencies to enable them to take on the role of school leader and school manager. The PPP consists of several stages, which are: proposal of principal candidates, selection, and education and training. Each stage of the PPP comes with certain requirements. This study focuses on the stage of education and training. The preconditions of this stage determine the success of the process of learning and the achievement of the learning goals. Based on this notion, this paper aims to describe the training readiness of teachers nominated as school principals, with particular regard to their physical, psychological, and material readiness. Further attention is given to proposing possible alternatives to improve PPP training readiness. The method used in this study is the descriptive qualitative method. Data were collected through pre-test and post-test, questionnaires, and document study. Descriptive statistics were employed to analyse the data. The analysis results show that, while teachers’ material readiness for training is relatively high, they lack psychological and physical readiness. Better time management, competent trainers, a contextual curriculum, and a matriculation programme are proposed as alternatives to improve psychological and physical readiness.